Konceptualizacja prawdy w świadomości językowej Polaków, Rosjan i Niemców (perspektywa aksjologiczna) - Rodziewicz, Barbara (Studia Rossica Posnaniensia, 2017)
The present article is an attempt at establishing a way of understanding the term 'truth', as well as characterizing all the phenomena the term encompasses in communities of Polish, Russian and German students. The author analyses the results of a Free Word Association Test.